Implementasi Pembelajaran Pendidikan Agama Islam Multikultural di MIN I Kota Malang - Mustafida, Fita (J-PAI: Jurnal Pendidikan Agama Islam, 2019)
Abstract. The spirit of national unity being tested now. Like violent conflicts in the name of religion, radicalism to terrorism. This is where the universal values of religion should be a driving force for humanity to build a more pluralist and inclusive religious understanding. Integrate of multiculturalism ideology in education is one of the efforts to provide education about pluralism and religious tolerance through schools (educational institutions). Therefore, multicultural Islamic education needs to be realized as a medium in providing solutions to conflicts caused by cultural differences in culture, religion, race, and other social conflicts. The aim of this study to describe, analyze, and interpret the implementation of multicultural Islamic education learning in Madrasah Ibtidaiyah Negeri (MIN) I Malang. The research approach uses was qualitative ethnographic types. The results showed that the learning process of Multicultural Islamic Religious Education was carried out by respecting and accommodating cultural diversity. So that it can be used as an ideal example of the application of Islamic Religious Education learning based on multicultural values, especially at the Islamic elementary school.Keywords: learning; Islamic education; multicultural.